DIETARY EVALUATIONS AND PALEOECOLOGY OF AN EXTINCT GIRAFFID (GIRAFFOKERYX PUNJABIENSIS) FROM SIWALIKS OF PAKISTAN - M. Tariq; N. Jahan (Journal of Animal and Plant Sciences, 2014)
The dietary preferences and paleoecology of Giraffokeryx punjabiensis Pilgrim, 1910, an extinct giraffid species from Chinji Formation of Potwar Siwaliks of Pakistan, have been investigated by incorporating mesowear-I, mesowear-II and hypsodonty methods. The mesowear patterns of Giraffokeryx punjabiensis are very much consistent with the browsers as well as seasonal mixed feeders whereas hypsodonty index (1.31 ± 0.06) categorizes it within the browsers. Comparison of the results from these research tools suggest that the extinct giraffid reflects diverse dietary spectra ranging from browsers to seasonal mixed feeders and shows no affinities with grazers. The coexistenceof G. punjabiensis with its mammalian paleocommunity reveals the persistence of mosaics of diverse habitats ranging from tropical evergreen forest to subtropical ones, closed seasonal woodlands to wooded savannas.
Keywords: hypsodonty; Miocene; mesowear; ungulates; Sivatherines; biostratigraphy